Synopsis of the genus Caperonotus Napp, 1993 (Coleoptera: Cerambycidae) - Napp, Dilma Solange; Monné, Miguel A. (Zootaxa, 2008)
The genus Caperonotus Napp, 1993 and the species C. cardinalis (Bates, 1870) and C. superbus (Aurivillius, 1897) are briefly redescribed. A new species, C. tucurui Napp & Monné sp. nov., described from Brazil (Pará), is added to the genus, widening its distribution in the Amazonic Region. All the species are illustrated and keyed.